Geodetic Innovation in Chilean Mining: The Evolution from Static to Kinematic Reference Frame in Seismic Zones - Caverlotti-Silva, M; Inzunza-Munoz, J (Walter de Gruyter GmbH, 2024)
The use of regional kinematic reference frames (mRFs) in seismic zones is uncommon worldwide. This article proposes a solution implemented for Chilean mining, whose current projects are based on the classic reference frames (PSAD56 and SAD69). The approach is to move from a classic reference frame to an mRF in seismic countries where earthquakes constantly alter the frame. Our research group calculated an mRF (REDGEOMIN) that includes interseismic, coseismic, and postseismic deformation using CORS with open data from 2009 to 2022 and processed with scientific standards global navigation satellite system. REDGEOMIN consists of a deformation model (ADELA) with an interpolation approach through thin plate spline, allowing the greatest deformation to be modelled at campaign points. The relationship between classical and modern systems was explored with conformal transformations and NTv2 grids to include deformations, especially coming from PSAD56 and SAD69. The results demonstrate that REDGEOMIN aligns with the IGb14 reference frame (<1.0 mm), SIRGAS (ENU = 1.0, 1, 0, 2.0 mm), and the Chilean national reference frame SIRGASChile@2021.00 (ENU = 1, 2, 1, 6, 4.3 mm) aligns with millimetric precision. ADELA deformation model accurately models period locations to within 5 mm. Densification of REDGEOMIN@2022.00 at passive points PSAD56/SAD69 shows centimetric precision. PSAD56/SAD69, adjusted in the 1970s, are outdated due to crustal movement and seismic events and have metric errors. Therefore, different types of transformations were evaluated between PSAD56/SAD69 and REDGEOMIN@2022, whose RMS is between 1.57 and 1.69 m, and national grid transformations (NTv2) with an RMS of 0.23 and 0.16 m for PSAD56 and SAD69, respectively. The relationship between the classic systems and REDGEOMIN allows the transformation of the entire Chilean mining cadastre to epoch 2022.00. Starting in 2022.00, REDGEOMIN/ADELA offers millimetre precision, which is crucial in seismic zones. Furthermore, it paves the way to implement an updated national-level mRF in case of seismic events. Currently, Chilean mining laws are rigid, geodesically speaking. Therefore, legal-technical suggestions for implementing REDGEOMIN are also included in this article. © 2024 the author(s), published by De Gruyter.